RECLAIMING LOCAL WISDOM FOR RELIGIOUS MODERATION: The Case of Buatulo Toulongo in Gorontalo, Indonesia - Andries Kango; Donald Qomaidiasyah Tungkagi (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2026)
This study investigates the role of Buatulo Toulongo as a local wisdom-based mechanism for countering religious radicalism in Gorontalo Province, Indonesia. The research addresses three questions: how the Buatulo Toulongo mechanism functions, what challenges threaten its sustainability, and how it can be revitalized as a strategy for promoting religious moderation. Using an institutional ethnography approach, the study was conducted in three regencies/municipalities through in-depth interviews, participant observation in fifteen mosques, and documentary analysis. The findings show that Buatulo Toulongo operates as a tripartite safeguard system at structural, cultural, and operational levels. Structurally, it creates checks and balances on religious authority; culturally, it transmits wasathiyyah values through local identity and communal traditions; operationally, it acts as an early warning system based on social capital and community networks. However, the mechanism faces significant challenges, including modernization, leadership regeneration crises, ideological competition, geographical vulnerability, and weak institutional support. The study concludes that revitalization requires integrated policy measures, including regional regulations, leadership cadre strengthening, curriculum integration, and gender inclusion. These findings highlight the strategic role of local wisdom in strengthening community resilience and advancing religious moderation in Indonesia.